Ribonuclease production by Aspergillus species - Gomes, E. (1998)
Ribonuclease production by Aspergillus flavipes. A sulphureus and A. fischeri in semisynthetic medium, after 24-144 hours at 30 degrees C under shaking, was studied. After cultivation, the medium was separated from micelia by filtration and the resultant solution was used as enzymatic extract. The highest amount of biomass and RNase was obtained after 96 hours of cultivation. The enzymes produced by three species presented similar characteristics, with optimum temperature at 55 degrees C and two peaks of activity at pH 4.5 and 7.0. A. flavipes RNases were more sensitive to temperature: 50% of the initial activity was lost after 1 hour at 70 degrees C. After this heat treatment, RNase of A. sulphureus lost 30% of this activity and that of A. fischeri only 16%. The nucleotides released by enzimatic hydrolysis of RNA were separated by ion exchange chromatography in a AG-1X8-formiate column and identified by paper chromatography. This procedure indicated that the raw enzymatic extract of Aspergillus flavipes is able to hydrolyze RNA, releasing 3'-nucleotides monophosphate at pH 4.5 and 3' and 5'-nucleotides monophosphate at pH 7.0 and 8.5. This result suggests that this strain produces two different types of RNase, one acidic and other alcaline, with different specificities.